2010
DOI: 10.1021/ja106405c
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Cancer Cells Using Click-Functionalized Polymer Capsules

Abstract: Targeted delivery of drugs to specific cells allows a high therapeutic dose to be delivered to the target site with minimal harmful side effects. Combining targeting molecules with nanoengineered drug carriers, such as polymer capsules, micelles and polymersomes, has significant potential to improve the therapeutic delivery and index of a range of drugs. We present a general approach for functionalization of low-fouling, nanoengineered polymer capsules with antibodies using click chemistry. We demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
157
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(164 citation statements)
references
References 9 publications
6
157
1
Order By: Relevance
“…We have also demonstrated the ability to encapsulate paclitaxel and doxorubicin in combination into polymersomes and have shown that polymersome mediated drug delivery increases the cytotoxicity compared to free drugs. The potential of superficially targeting tumour cells by conjugating tumour-specific ligands to the surface of polymersomes 48 may further decrease offtarget cytotoxicity and reduce the levels of drugs needed to achieve systemic coverage. Table 1.…”
Section: Cellular Internalisation Kineticsmentioning
confidence: 99%
“…We have also demonstrated the ability to encapsulate paclitaxel and doxorubicin in combination into polymersomes and have shown that polymersome mediated drug delivery increases the cytotoxicity compared to free drugs. The potential of superficially targeting tumour cells by conjugating tumour-specific ligands to the surface of polymersomes 48 may further decrease offtarget cytotoxicity and reduce the levels of drugs needed to achieve systemic coverage. Table 1.…”
Section: Cellular Internalisation Kineticsmentioning
confidence: 99%
“…Such capsules sensitive to external conditions e.g., magnetic field should contain magnetic particles [281] or they have special receptor molecules like antibodies (Ab) attached to the outer side of the shell [282]. The Ab can be adsorb by electrostatic interactions [283] or covalently liked to surfaces [284][285][286][287][288]. For uncharged materials like poly(ethylene glycol) (PEG) or poly(N-vinylpyrrolidone) (PVPON) covalent attachment of the Ab is required since electrostatic attachment is not effective for lowfouling materials because they inhibit nonspecific protein binding.…”
Section: Stimulus Responsive Shell-tuning Capsules For Drug Deliverymentioning
confidence: 99%
“…The pre-condensation of pDNA with peptides improves lipid-based delivery systems and transfection efficiencies [326]. At last, by using LbL method Caruso et al [284][285][286][287][288] synthesized redoxactive polymeric microcapsules with the cross-linked shell containing disulfide bonds for the delivery of a siRNA targeting to PC-3 prostate cancer cells. The polycation-polylysine (PLL) for a siRNA complexation was infiltrated into the pores of nanoporous silica particles prior to an assembly of layer from the negatively charged poly(methacrylic acid) with thiol-modified groups (PMASH).…”
Section: Polymer Micelles and Capsules Loaded With Fluorescent Therapmentioning
confidence: 99%
“…88 This unique feature is often referred to as a "stealth" effect, since opsonisation by macrophages and non-specific binding to cells is dramatically decreased. 89 Moreover, due to their soft architecture, microgels are able to flatten themselves onto vascular surfaces, thus simultaneously anchoring in multiple points. Thereby, their retention in the targeted disease site is enhanced.…”
Section: Microgels For Loading and Release Applicationsmentioning
confidence: 99%